Inorganic nanostructures decorated graphene - Lim, Hong Ngee (InTech, 2013)
The unique properties of graphene, a single-atom-thick sheet of sp2-hybridized carbon atoms with honeycomb structure, have ensured it is the subject of significant number of papers detailing its synthesis, properties and applications. In this chapter, the recent trends in the synthesis methodologies of graphene-inorganic nanostructures are presented and their impact on various applications reviewed.